Astragalus mongholicus Bunge and Panax notoginseng (Burkill) F.H. Chen Formula for Renal Injury in Diabetic Nephropathy-In Vivo and In Vitro Evidence for Autophagy Regulation - Dan Wen; Dan Wen; Rui-Zhi Tan; Chang-Ying Zhao; Jian-Chun Li; Xia Zhong; Hui Diao; Hui Diao; Xiao Lin; Dayue Darrel Duan; Jun-Ming Fan; Jun-Ming Fan; et al. (Frontiers Media S.A., 2020)
BackgroundDiabetic nephropathy (DN) is a serious complication of diabetes mellitus (DM) with limited treatment options. DN leads to progressive renal failure and accelerates rapidly into end-stage renal disease. Astragalus mongholicus Bunge and Panax notoginseng (Burkill) F.H. Chen formula (APF) is a traditional Chinese medicine (TCM) formula widely used to treat chronic kidney diseases (CKD) in the clinic in the southwest of China. The aim of this study is to explore how APF and its related TCM theory work on DN and whether mTOR/PINK1/Parkin signaling plays a part in this process.MethodsHPLC was used for preliminary chemical analysis and quantitative analysis of the five components of APF. An in vivo autophagy deficiency model was established in C57BL/6 mice by streptozocin (STZ) combined with a high-fat and high-sugar diet, while the in vitro autophagy deficiency model was induced with high glucose (HG) in renal mesangial cells (RMCs). Renal histopathology staining was performed to investigate the extents of inflammation and injury. Real time-PCR and Western blotting techniques were utilized to assess autophagy-related proteins.ResultsAPF significantly ameliorated renal injury in DN mice, specifically restoring blood urea nitrogen, serum creatinine, and 24-hour albuminuria. APF also reduced the mRNA and protein expressions of TNFα, IL-1β, and IL-6 in STZ-induced DN mice. Furthermore, APF improved the autophagy deficiency induced by STZ in vivo or HG in vitro, as revealed by changes in the expressions of mTOR, PINK1, Parkin, Beclin 1, p62, and LC3B. Notably, inhibition of autophagy with 3-methyladenine in APF-treated RMCs aggravated cellular damage and altered mTOR/PINK1/Parkin signaling, indicating that APF rescued HG damage through promoting autophagy.ConclusionAPF may protect the kidneys from inflammation injuries in DN by upregulating autophagy via suppressing mTOR and activating PINK1/Parkin signaling. This experimental evidence strongly supports APF as a potential option for the prevention and treatment of DN.